A proposal to use a balanced scorecard to evaluate Information for Health: an information strategy for the modern NHS (1998–2005) - Protti, Denis (Computers in biology and medicine, 2002)
The author was invited to assist in the development of an evaluation methodology for the Strategy. One of the conundrums of measuring the information management & technology (IM&T) function is that infrastructure investments cannot be cost justified on a return on investment basis. The balanced scorecard (BSC) is a means to evaluate corporate performance from four different perspectives: the financial perspective, the internal business process perspective, the customer perspective, and the learning and growth perspective. An IM&T BSC for Information for Health was recommended as means of allowing managers to see the positive and negative impacts of IM&T activities on the factors that are important to the NHS as a whole.